2018
DOI: 10.1111/jgs.15683
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Risk for Adverse Outcomes in Older Adults: The Need to Include Both Physical Frailty and Cognition

Abstract: BACKGROUND: Physical frailty is a powerful tool for identifying nondisabled individuals at high-risk of adverse outcomes. The extension to which cognitive impairment in those without dementia adds value to physical frailty in detecting high-risk individuals remains unclear. OBJECTIVES: To estimate the effects of combining physical frailty and cognitive impairment without dementia (CIND) on the risk of basic activities of daily living (ADL) dependence and death over eight years. DESIGN: Prospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
72
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 48 publications
7
72
0
2
Order By: Relevance
“…Both frailty and cognitive impairment are risk factors for future adverse outcomes, such as dementia, disability, hospitalization and death. These outcomes have been confirmed in Brazilian and non-Brazilian older adults 42, 43,44,45 .…”
Section: Crude Modelmentioning
confidence: 55%
“…Both frailty and cognitive impairment are risk factors for future adverse outcomes, such as dementia, disability, hospitalization and death. These outcomes have been confirmed in Brazilian and non-Brazilian older adults 42, 43,44,45 .…”
Section: Crude Modelmentioning
confidence: 55%
“…Cross-sectional and longitudinal research has demonstrated that older adults with physical frailty exhibit poorer cognitive performance and greater risk of cognitive decline and dementia than individuals without frailty (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and that individuals with cognitive decline or dementia show a higher risk of physical frailty (16)(17)(18). It has also been demonstrated that the coexistence of physical frailty and cognitive impairment (cognitive frailty), ranging from 1 to 5% in community-dwelling older adults (19), increases the risk of mortality (20)(21)(22)(23)(24)(25), functional disability (26), and incident neurocognitive disorders (9,27) in later life. Importantly, the rates of change of frailty and cognition over time are strongly correlated and associated with the same brain pathologies, such as the presence of macroinfarcts, Alzheimer's disease pathology, and nigral neuronal loss (28).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a greater annual rate of change in frailty is associated with a subsequent development of Alzheimer's disease . Physical function and cognitive impairment were shown to be independent predictors of incident disability and death in older adults without cancer, and when cognitive measures are added to frailty assessment, the combination was better at identifying vulnerable older adults at risk of future activities of daily living dependence …”
mentioning
confidence: 99%
“…12 Physical function and cognitive impairment were shown to be independent predictors of incident disability and death in older adults without cancer, and when cognitive measures are added to frailty assessment, the combination was better at identifying vulnerable older adults at risk of future activities of daily living dependence. 13 Given our aging population, the prevalence of cancer, and the association of cognitive impairment with frailty in older adults, improved understanding of the relationships between frailty and cognition in cancer is critical for managing these risk factors. [14][15][16][17] This analysis evaluates frailty and its relation to cognition longitudinally over the course of adjuvant chemotherapy and up to 6 months postchemotherapy, in patients with breast cancer aged 50 years and older, including both subjective and objective assessments of cognition.…”
mentioning
confidence: 99%